Pelatihan Dan Pendampingan Pencatatan Laporan Keuangan Berbasis Digital Pada UMKM Gudeg Mbah Djo - Zainnita Julia Qhoirunnisa; Zaenal Wafa (Akuntansi, 2023)
This community service activity was carried out to provide training and assistance regarding the preparation of financial reports for the Gudeg Mbah Djo UMKM in Kulon Progo Regency. In its financial records, the financial reports of UMKM Gudeg Mbah Djo are still recorded conventionally, so that there is often no clear separation between personal money and company money. Owners also do not know exactly how much profit or loss they have from the business they are running because so far it has only been ‘niteni’. The reason is because the owner still does not understand the importance of financial reports and the basis for recording them. From these main issues, it is necessary to carry out training and assistance for preparing financial reports for the Gudeg Mbah Djo UMKM.